2018
DOI: 10.1016/j.drugalcdep.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Multicomorbidity of chronic diseases and substance use disorders and their association with hospitalization: Results from electronic health records data

Abstract: Background: Chronic diseases are prevalent and the leading causes of mortality. Comorbidity of substance use disorders (SUDs) and chronic diseases is understudied to inform behavioral healthcare integration. Objectives: This study leveraged electronic health record (EHR) data of 211,880 adults from a large health system to examine prevalence and correlates of comorbidity of SUDs and nine chronic disease groups and to determine their association with hospitalization. Methods: Logistic regression analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 36 publications
6
88
2
Order By: Relevance
“…In bivariate analyses of high-risk opioid users, these calculations were performed separately for each of the two age groups. Characteristics included in these analyses were chosen from literature review, specifically based on (a) those reported by Hirschtritt et al as significant predictors of opioid-benzodiazepine use compared with opioid use alone, such as substance use disorder, anxiety, and depression, plus (b) risk factors (e.g., diabetes, hypertension) and diagnoses for cardiovascular or respiratory diseases, which are often chronically comorbid with substance use disorders (Wu et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In bivariate analyses of high-risk opioid users, these calculations were performed separately for each of the two age groups. Characteristics included in these analyses were chosen from literature review, specifically based on (a) those reported by Hirschtritt et al as significant predictors of opioid-benzodiazepine use compared with opioid use alone, such as substance use disorder, anxiety, and depression, plus (b) risk factors (e.g., diabetes, hypertension) and diagnoses for cardiovascular or respiratory diseases, which are often chronically comorbid with substance use disorders (Wu et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The variables included in this study were socio-demographic factors (sex [4], age, marital status, insurance type [2], patients' residency (urban/rural) (based on their postal codes and the city planning of Beijing)); primary diagnostic categories (ICD 10 codes: depressive disorder (F32-F33), bipolar disorder (F31), schizophrenia and related disorder (F20-F29), substance use disorder (F10-F19), and other psychiatric disorders); number of medical comorbidities [14] (31 comorbidities defined in the AHRQ Elixhauser comorbidity index [14,34,35] were identified using the Stata module "ELIXHAUSER" and counted); treatment-related factors (use of electroconvulsive therapy (ECT) [15] (identified by the ICD-9-CM-3 code for ECT, 94.27)); previous admission(s) 1 year prior to the index admissions [5] (none, 1 times, 2 times, 3 times or more) (matched using patient identifier across hospitals and years); length of stay (days); as well as institutional factors [5,15], including hospital level (tertiary or secondary) and hospital location (urban or rural). The comorbidities listed in the Elixhauser comorbidity index included cardiovascular conditions liver and renal diseases [36] (See Supplementary Table 1 in Additional File 1 for details). The Elixhauser comorbidity index has been used previously in riskadjustment methodologies and predictive models [34].…”
Section: Independent Variablesmentioning
confidence: 99%
“…Cluster 10 (Substance addiction, n = 685) includes patients with substance dependence disorders: alcohol disorders (35%) and nicotine dependence (99.3%), both previously studied as diagnoses associated with depression [29,36].…”
Section: Cluster Analysismentioning
confidence: 99%